Livestock breeding, conservation and genomics in Brazil: Who, when, where, and what - McManus, Concepta; de Albuquerque, Lucia Galvão [UNESP]; Dias, Laila Talarico; Paiva, Samuel Rezende; Pimentel, Daniel; Pimentel, Felipe (Elsevier, 2024)
We examined Brazilian animal breeding and genetics publishing patterns to identify the major research groups and where they publish. Data was collected in Scopus and analysed in Vosviewer (version 1.615, 2020). The analyses showed that this area of knowledge is centred on groups in São Paulo state universities. Most research is on classical quantitative genetics published in Brazilian journals with a lower impact (impact factor lower than the world mean of one). Beef cattle are the main species researched, with dairy cattle and sheep also present. Less information is available on goats, poultry, swine, and equines. Research must expand to regions outside São Paulo State and beyond classical quantitative genetics. Publishing should be directed towards international journals and an increase in international collaborations. We also use the data to discuss and suggest new research areas to improve Brazil´s food security and increase sustainable animal production.
Keywords: Authors; Bibliometric analyses; Citation; Coupling; Livestock